Can Paradoxical Leadership Revert Silence Imposed by Corporate Hypocrisy and Organizational Inertia Bring in Voice Behavior: An Examination Using SEM - M. M. Sulphey; K. Mohamed Jasim (SAGE Open)
Corporate hypocrisy (CH), organizational inertia (OI), and silence are undoubtedly issues many organizations have faced recently. Effective management of these paradoxes requires a different type of leadership. Based on the Paradox theory, Information Manipulation theory, and a few other related theories, the authors propose paradoxical leadership (PL) as an ideal style to deal with such situations in the current volatile and uncertain business environment. The study examined whether PL can revert silence induced by CH and OI to make employees air their voices and facilitate good performance. Data for the study was collected from 617 (response rate of 88.14%) gainfully employed samples. The data was analyzed using Structural Equation Modeling (SEM). Results show that PL can moderate the relationship between employee silence induced by CH and OI and facilitate voice behavior. The study also presented a few plausible suggestions that organizations could adopt to deal with silence and induce voice. The study is expected to stimulate heightened research interest in the fecund area.